Vascular wilt of teak (Tectona grandis) caused by Fusarium oxysporum in Brazil - BORGES, Rafaela; MACEDO, Mônica; CABRAL, Cléia; ROSSATO, Maurício; FONTES, Maria; SANTOS, Maria; FERREIRA, Maria; FONSECA, Maria; REIS, Ailton; BOITEUX, Leonardo (Phytopathologia Mediterranea, 2018)
Commercial plantations of teak (Tectona grandis L.f.) are affected by many economically important fungal diseases under Brazilian conditions. Teak plants exhibiting distinctive vascular wilt symptoms were observed in Mirassol do Oeste (MT), Brazil. Trunk samples of the affected trees were collected, disinfected, and plated onto potato dextrose agar. Fungal cultures obtained displayed morphological characteristics typical of the Fusarium oxysporum species complex. A representative F. oxysporum isolate was used in pathogenicity assays. Teak plants displayed symptoms similar to those observed under field conditions approx. 60 d after root-dipping inoculation. Amplicons corresponding to segments of the translation elongation factor 1-α (TEF-1α) and RNA polymerase II second largest subunit (RPB2) genes were obtained using as template the genomic DNA extracted from two Fusarium isolates obtained from teak. Phylogenetic analyses of the amplicon sequences placed the isolates into the same cluster of isolates belonging to the F. oxysporum species complex. To our knowledge, this is the first report of vascular wilt of teak caused by F. oxysporum in the Neotropical region.